In Vivo Reflectance Confocal Microscopy Applied to Acral Melanocytic Lesions: A Systematic Review of the Literature - Chello, Camilla; Cappilli, Simone; Pellegrino, Luca; Michelini, Simone; Palmisano, Gerardo; Gemma, Giuseppe; Salvi, Marisa; Cantisani, Carmen; Di Stefani, Alessandro; Peris, Ketty; Pellacani, Giovanni (Diagnostics (Basel), 2024)
Background: Acral melanocytic lesions often pose a diagnostic and therapeutic challenge for many clinicians. Reflectance confocal microscopy (RCM) is an imaging technique widely used for the assessment of skin cancers. The aim of this review is to explore the applicability of RCM for the diagnosis of nevi and melanoma on the acral sites. Methods: Study selection was conducted based on the application of RCM for acral melanocytic lesions. All types of articles (original articles, short reports, and single case reports) were included in the analysis following PRISMA updated guidelines. Results: The search retrieved 18 papers according to the selection criteria; after removing duplicate records and additional articles by one or more of the exclusion criteria, a total of seven studies were carefully evaluated. Conclusions: RCM seems a valuable and useful additional tool for the diagnosis of acral melanocytic lesions, and its use may decrease the need for invasive procedures to some extent. Visualization of deeper layers may be achieved through mechanical removal of the superficial stratum corneum.